CHARACTER EDUCATION MODEL BASED ON EDUCATION IN ISLAMIC BOARDING SCHOOL - Perdana, Novrian Satria (EDUTECH, 2015)
Abstract, Various efforts to make education more meaningful for individuals concerning affective domain has been conducted through several subjects, including Religion Education, Civics Education, Social Sciences Education, Indonesian Language Education, and Physical Education. However, those efforts could not effectively hold character building which is dynamic and adaptive to fast changing era. The failure of character building at formal school must be anticipated, so it is necessary to develop relevant teaching model and education system. The problem of character education in school which is not yet able to build students’ character is affected by several factors: school management, teacher, and learning model. Some researches on best practices of character educationhave been conducted in order to obtain relevant teaching model at several Islamic boarding schools in North Sumatera Province, Nangroe Aceh Darussalam Province, West Sumatera Province, Riau Province, Jambin Province and South Sumatera Province. The data was collected using indepth-interview and observation. It was found that salafiyah Islamic boarding school put more priority on teacher (ustadz) role model, while modern Islamic boarding school applied tight rules to develop students’ discipline, and responsibility. Islamic boarding schools build the characters of caring for other people, sincerity of devotion, modesty, and independence. The policy that could be suggested based on this research is that of the application of character education must be holistically embedded in school program and must be comprehended and obeyed by school’s educators and students alikeBetter implementation could be achieved if the character education is explicitly formulated in the mission statement of the school.   Keywords:  character education, learning model, Islamic boarding school  Abstrak, Berbagai upaya untuk menjadikan pendidikan lebih mempunyai makna bagi individu yang menyentuh tataran afektif telah dilakukan melalui mata pelajaran Pendidikan Agama, Pendidikan Kewarganegaraan, Pendidikan IPS, Pendidikan Bahasa Indonesia, dan Pendidikan Jasmani. Namun demikian upaya-upaya tersebut ternyata belum mampu mewadahi pengembangan karakter secara dinamis dan adaptif terhadap perubahan jaman yang sangat cepat. Permasalahan gagalnya pendidikan formal di sekolah dalam membentuk karakter siswa sangat perlu diantisipasi, sehingga perlu dikembangkan suatu model pembelajaran dan system pendidikan yang dapat digunakan untuk membentuk karakter siswa. Permasalahan pendidikan di sekolah yang belum dapat membentuk karakter siswa dipengaruhi oleh beberapa factor, diantaranya factor manajemen sekolah, guru, dan model pembelajaran. Untuk memperoleh model pembelajaran yang cocok, telah dilakukan penelitian tentang best practices pendidikan karakter di beberapa pesantren yang berada di propinsi Sumatera Utara, propinsi Nangroe Aceh Darussalam, propinsi Sumatera Barat, propinsi Riau, propinsi Jambi, dan propinsi Sumatera Selatan. Pengumpulan data dalam penelitian ini dilakukan dengan dua tehnik yang lazim digunakan dalam penelitian dalam penelitian kualitatif, yaitu; observasi dan wawancara mendalam. Ditemukan bahwa pesantren salafiyah lebih mengutamakan keteladanan ustadz, sedangkan pesantren modern menerapkan aturan yang ketat untuk menumbuhkan sikap disiplin dan tanggungjawab. Pesantren menumbuhkan atribut karakter saling tolong menolong, ihklas mengabdi, kesederhanaan, dan kemandirian. Kebijakan yang dapat diambil berdasarkan hasil penelitian ini adalah menerapkan pendidikan karakter secara holistic melalui program sekolah yang harus dipahami dan dipatuhi oleh semua unsur pendidik dan peserta didik.  Untuk itu, lembaga pendidikan seharusnya menetapkan misi yang eksplisit terkait pengembangan karakter siswa.  Kata Kunci: pendidikan karakter, model pembelajaran, pondok pesantren